2016
DOI: 10.1111/jep.12565
|View full text |Cite
|
Sign up to set email alerts
|

Hospital pharmacy medication reconciliation practice in Jordan: perceptions and barriers

Abstract: This study demonstrates a relatively low awareness of the concept and policy of medication reconciliation process among Jordanian pharmacists. This suggests that educational programs are urgently needed to increase pharmacists' role and responsibilities in implementing and practicing reconciliation services with expected positive impact on patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…A previous study, not directly focusing on medication reconciliation, showed that student pharmacists and faculty identified more than 1000 medication-related problems, 4.3% of which were related to medication reconciliation [27]. A study assessing hospital pharmacy medication reconciliation practice in Jordan (a neighboring country) showed relatively low awareness of the concept and policy of medication reconciliation process among Jordanian pharmacists [28]. To our knowledge, there are no published studies addressing medication reconciliation in Lebanon.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study, not directly focusing on medication reconciliation, showed that student pharmacists and faculty identified more than 1000 medication-related problems, 4.3% of which were related to medication reconciliation [27]. A study assessing hospital pharmacy medication reconciliation practice in Jordan (a neighboring country) showed relatively low awareness of the concept and policy of medication reconciliation process among Jordanian pharmacists [28]. To our knowledge, there are no published studies addressing medication reconciliation in Lebanon.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies are available on the value and practice of medication reconciliation from health care institutions outside USA and Europe. A recent study demonstrated a relatively low awareness of the concept and policy of medication reconciliation process among pharmacists (Hammour et al, 2016). There are also hardly any data from Saudi Arabia and from developing countries that discuss medication reconciliation process at discharge from the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The image on the current practice of medication reconciliation is not clear in Jordan; that is why many healthcare providers were not aware of the medication reconciliation concept. This was evident in a previous study by Abu Hammour et al, which showed a low level of awareness and understanding about the medication reconciliation process among Jordanian hospital pharmacists [33]. Low awareness about medication reconciliation in Jordan may be due to the lack of training workshops, scientific meetings or conferences, the lack of university curricula focusing on the extra roles that can be played by the pharmacists.…”
Section: Discussionmentioning
confidence: 97%